Implementation of Maqashid al-Syariah in Islamic Criminal Law in Muslim Countries: A Comparative Study in Saudi Arabia, Iran, Malaysia, and Indonesia - Muhammad Arafat; Asmuni (AL-SULTHANIYAH, 2025)
This article analyzes the implementation of Maqasid Syariah in criminal law in four. This research examines the implementation of Maqashid Sharia in Islamic criminal law in Saudi Arabia, Iran, Malaysia and Indonesia by highlighting the variations in implementation based on each country's legal system. Saudi Arabia and Iran fully implement Islamic criminal law, while Malaysia and Indonesia adopt it to some extent through their national legal systems. This study also assesses the extent to which Islamic criminal law in the four countries safeguards the five main aspects of Maqashid Sharia, namely religion, soul, mind, offspring, and property, and examines its effectiveness in upholding justice and social order. The main research question posed is: how is Maqasid Syariah implemented in the criminal law systems in these countries, and to what extent are these principles in line with human rights and national law? This study uses a qualitative approach with a library study method, where data is obtained from academic literature, legal documents, and related articles. The research findings show that the implementation of Maqasid Syariah varies from country to country depending on their respective socio-political contexts. The study found that the implementation of Maqashid Sharia in Islamic criminal law in Saudi Arabia, Iran, Malaysia and Indonesia varies, with Saudi Arabia and Iran implementing it strictly, while Malaysia and Indonesia adopted it in a dual legal system. The academic contribution lies in the comparative analysis of the effectiveness of Islamic criminal law in achieving justice and the challenges of harmonization with human rights. Its application can be a reference for policy makers in designing a more adaptive Islamic criminal law system, balanced between Islamic law and the demands of modernity.